Representation and use of indigenous heritage constructs : implications for the quality and relevance of heritage education in post colonial southern Africa - Zazu, Cryton (Rhodes University, Faculty of Education, Department of Education, 2013)
This study explores representation and use of indigenous heritage constructs with a view to identifying implications thereof for the quality and relevance of heritage education practices in post colonial southern Africa. Framed within a critical hermeneutic research paradigm under-laboured by critical realist ontology, the study was conducted using a multiple case study research design. The data collection protocol was three-phased, starting with a process of contextual profiling, within which insights were gained into discourses shaping the constitution and orientation of heritage education practices at the Albany Museum in South Africa, the Great Zimbabwe Monument in Zimbabwe and the Supa Ngwao Museum in Botswana. The second phase of data collection entailed modelling workshops in which educators engaged in discussion around the status of heritage education in post apartheid South Africa. This highlighted, through modelled lessons, some of the tensions, challenges and implications for working with notions of social transformation and inclusivity in heritage education. The third phase of data collection involved in-depth interviews. Twelve purposively selected research participants were interviewed between 2010 and 2011. Data generated across the study was processed and subjected to different levels of critical discourse analysis. Besides noting how heritage education in post colonial southern Africa is poorly framed and under-researched, this study revealed that current forms of representing indigenous heritage constructs are influenced more by socio-political discourses than the need to protect and conserve local heritage resources. The study also noted that the observed heritage education practices are oriented more towards addressing issues related to marginalisation and alienation of indigenous cultures and practices, than enhancing learners' agency to manage and utilise local heritage resources in a more sustainable ways. Based on these findings the study recommends re-positioning heritage education within the framework of Education for Sustainable Development (ESD). ESD acknowledges both issues of social justice and the dialectical interplay between nature and culture; as such, it may allow for representation and use of indigenous heritage constructs in ways that expand current political orientations to include sustainability as an additional objective of heritage education. Given that little research focusing on heritage education has been undertaken within southern Africa, the findings of this study provide a basis upon which future research may emerge.
Keywords: Albany Museum (Grahamstown) -- South Africa); Cultural property -- Conservation and restoration -- Research -- Africa, Southern; Great Zimbabwe (Extinct city); Indigenous peoples -- Material culture -- Africa, Southern; Anthropological museums and collections -- Management -- Research -- Africa, Southern; Cultural property -- Management -- Research; Ethnoscience -- Study and teaching -- Africa, Southern